The Contingent Value of Local Partners' Business Group Affiliations - Lu, Jane W.; Ma, Xufei (Academy of Management Journal, 2008)
We investigated the value of local partners' business group affiliations in international joint ventures (IJVs) by integrating economic and political perspectives on business groups with insights from the IJV literature. In 563 Sino-Japanese IJVs in China, we found that a local partner's affiliation to a regional business group enhances the performance of an IJV when its location restricts foreign direct investment (FDI). Meanwhile, a local partner's affiliation to a national business group enhances the performance of an IJV when it operates in an FDI-restricted industry. Our findings point to the contingent value of business group affiliation in emerging economies.